2008
DOI: 10.1007/s11274-008-9731-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of culture conditions on the production of ligninolytic enzymes by white rot fungi Phanerochaete chrysosporium (ATCC 20696) and separation of its lignin peroxidase

Abstract: The present work was carried out to determine the optimum culture conditions of Phanerochaete chrysosporium (ATCC 20696) for maximizing ligninolytic enzyme production. Additionally, separation of its lignin peroxidase was conducted. After experiments, an optimized culture medium/condition was constructed (per liter of Kirk's medium): dextrose 10 g, ammonium tartrate 0.11 g, Tween-80 0.5 g, MnSO 4 7 mg, and veratryl alcohol 0.3 g in 10 mM acetic acid buffer pH 4.5. Under the optimized experimental condition, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…These enzymes are secreted during secondary metabolism, as a result of nutrient depletion of carbon or sulphur, or especially, manganese and nitrogen (Hamman et al, 1997;Leung and Pointing, 2002). Other factors are also implicated, such as initial pH of the medium and incubation temperature , the level of aeration and agitation during incubation, the availability of mediator compounds and metals (Leung and Pointing, 2002;Mouso et al, 2003;Cordi et al, 2007), or the presence and concentration of surfactants (Rodríguez Couto et al, 2000;Ürek and Pazarlioğlu, 2005;Wang et al, 2008).…”
Section: Effect Of Biosurfactants On the Degradation Of Hydrophobic Omentioning
confidence: 99%
“…These enzymes are secreted during secondary metabolism, as a result of nutrient depletion of carbon or sulphur, or especially, manganese and nitrogen (Hamman et al, 1997;Leung and Pointing, 2002). Other factors are also implicated, such as initial pH of the medium and incubation temperature , the level of aeration and agitation during incubation, the availability of mediator compounds and metals (Leung and Pointing, 2002;Mouso et al, 2003;Cordi et al, 2007), or the presence and concentration of surfactants (Rodríguez Couto et al, 2000;Ürek and Pazarlioğlu, 2005;Wang et al, 2008).…”
Section: Effect Of Biosurfactants On the Degradation Of Hydrophobic Omentioning
confidence: 99%
“…[18,19] Aromatic compounds structurally related to lignin, such as xylidine, ferulic acid and veratric acid, are routinely added to fungal cultures to increase laccase production. [12,15,20,21] The regulation of laccase expression by metals is widespread in fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this fact they suggested that certain functional variability is needed; the main additional reason for the splitting in many isoenzymes is thought to be excessive glycosylation. Many researchers reported isoenzymes of multiple LiPs from whiterot fungi species Kirk, 1988 andWang et al, 2008).…”
Section: Ion Exchange Chromatographymentioning
confidence: 99%